Pengaruh Nilai Tukar Uang, Jumlah Uang Beredar dengan Kegiatan Export Terhadap Inflasi Pada Masa Pandemic Covid-19 - Suginam Suginam; Elmira Siska; Syahrijal Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Covid-19 causes many changes and economic turmoil of a country to be very difficult and also greatly affects world trade, this study looks at some of the effects of the dollar exchange rate in the form of rupiah and the amount of money circulating in the world market which is related to textile export activities. during the pandemic these things are associated with the effect on inflation where inflation is a condition that determines the price of goods in the country increases or decreases, the impact shown between the independent variables on the dependent variable in a direct or indirect effect relationship, the results of this study are